Survival rate and Abnormality Larvae of Silver Pompano fish (Trachinotus blochii) On Different Salinity - Astutiwati; Amir, Sadikin; Nurliah; Alamsjah, Mochammad Amin (Department of Aquaculture, 2025)
Silver pompano (Trachinotus blochii) is a species of marine aquaculture are still new in Indonesia. This species has a life cycle that is entirely at sea, but has the potential to be cultivated in ponds of low salinity. This study was conducted to determine the effect of different salinity on larval rearing on the survival rate and degree of abnormality larvae silver pompano fish larvae (T. blochii). This research was conducted in June 2014 in Lombok Marine Aquaculture Development Center Aquaculture Department Directorate General for Maritime Affairs and Fisheries Station Sekotong, West Lombok regency, West Nusa Tenggara Provinceby using a completely randomized design (CRD), which consists of five salinity treatments (34, 31, 28, 25, and 22 ppt) with 5 replications. The results showed that silver pompano fish larvae age Save D17-D35 is able to survive at salinity 22-34 ppt with a survival rate of over 90%. However, in less than 31 ppt salinity, larvae abnormality silver pompano Save increased with decreasing salinity. Keywords: Survival rate, abnormality, Silver pompano, salinity.